Pharma Guard: Smart Medication Management System - Louay Al Nuaimy; Abrar Al Hosni; Ahad Al Wahaibi (International Journal of Mobile Computing Technology, 2024)
Pharma Guard Smart Medication Management System presenting a comprehensive overview of an innovative technology designed to revolutionize medication management in healthcare settings. In an era of advancing digital solutions, the Pharma Guard system offers a sophisticated approach to ensuring medication safety and adherence. Through the integration of smart technology, including internet of things (IoT) devices and machine learning algorithms, Pharma Guard enables real-time monitoring, tracking, and management of medication consumption by patients. This paper outlines the key features and functionalities of Pharma Guard, highlighting its potential to mitigate medication errors, improve patient outcomes, and streamline healthcare workflows. Additionally, the paper discusses the implementation challenges and considerations associated with deploying Pharma Guard in diverse healthcare environments. While canceling traditional prescriptions and converting them to electronic format can facilitate communication between the patient and the health facility and enhance smooth communication between prescriptions and pharmacy staff about discontinued medications, there is little work that can be explored to meet the needs of pharmacy staff users. The purpose of this research: This study makes use of qualitative interviews with pharmacy staff to address the following question: When a physician makes changes to a medication, using what information do pharmacy staff need to make correct and effective decisions in their medication management roles? We performed an inductive thematic analysis of interviews with numerous pharmacy staff members, comprising pharmacists and pharmacy technicians, at diverse outpatient community pharmacy locations within an academic health district. Both pharmacists and pharmacy technicians consistently identified three themes of information needs: understanding the prescriber's intention when initiating treatment, clinical justification for medication change, and the intended medication regimen. It was observed that traditional electronic health record (EHR) systems often fail to fully address these multiple information needs, hindering the common goals of accurately dispensing medications and supporting patient self-management. Our qualitative analysis indicates that outpatient community pharmacy staff within an academic health system frequently require additional information from the EHR following medication changes to meet their information needs effectively. Ideally, prescribers should have access to enough information to automatically recognize all discontinued prescriptions. These limitations highlight the significance of developing functionalities that enable the regular exchange of essential information during medication changes, such as structured data elements.
Keywords: Smart medication management system; electronic health record (EHR); healthcare workflows